2014
DOI: 10.1111/jfb.12561
|View full text |Cite
|
Sign up to set email alerts
|

Validation of daily microincrement deposition in otoliths of juvenile and adult Peruvian anchovy Engraulis ringens

Abstract: Wild adult specimens of the Peruvian anchovy Engraulis ringens were captured and reared to validate the daily periodicity of otolith microincrement formation. The postcapture stress generated spontaneous spawning, making it possible to conduct a rearing trial on larvae first in an artificial nutrient-enriched system (ANES) for 52 days followed by an artificial feeding regime in a culture tank until day 115 post-hatch. Microincrements of the sagittal otoliths of sacrificed juveniles [mean ± S.D. total length (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…Cermeño et al (2008) concluded that GBR was the most reliable ageing procedure for E. encracicolus. Conversely, Plaza and Cerna (2015) reported a closer correspondence between daily age and number of increments when double rings were counted separately in juvenile E. ringens produced under rearing conditions, although double rings were restricted only to the transition zone (i.e. Zone B) and consequently age underestimation was marginal.…”
Section: Otolith Microstructural Featuresmentioning
confidence: 90%
See 3 more Smart Citations
“…Cermeño et al (2008) concluded that GBR was the most reliable ageing procedure for E. encracicolus. Conversely, Plaza and Cerna (2015) reported a closer correspondence between daily age and number of increments when double rings were counted separately in juvenile E. ringens produced under rearing conditions, although double rings were restricted only to the transition zone (i.e. Zone B) and consequently age underestimation was marginal.…”
Section: Otolith Microstructural Featuresmentioning
confidence: 90%
“…However, under rearing conditions, the identification of micro-structural zones in E. ringens was very distinctive (Plaza and Cerna 2015) compared with otolith microstructure of wild juveniles where boundaries between zones are not easily identified. Hence, the use of GBR is far more consistent for the identification of primary micro-increments in wild specimens.…”
Section: Otolith Microstructural Featuresmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous experiences with other species indicate that, given suitable reproductive conditions, the stress of being caught may trigger spontaneous spawning in adults within 24 h of capture (Cleary et al 2002, Plaza & Cerna 2015. Because the catches occurred during the reproductive period peak for Patagonian sprat (Leal et al 2011), it was expected that the specimens would have spawned spontaneously within the first day in captivity.…”
Section: Resultsmentioning
confidence: 99%